2021
DOI: 10.1093/eurjcn/zvaa030
|View full text |Cite
|
Sign up to set email alerts
|

Effects of the non-contact cardiopulmonary resuscitation training using smart technology

Abstract: Aims Accurate cardiopulmonary resuscitation (CPR) performance is an essential skill for nursing students so they need to learn the skill correctly from the beginning and carry that forward with them into their clinical practice. For the new normal after coronavirus disease 2019 (COVID-19), safe training modules should be developed. This study aimed to develop non-contact CPR training using smart technology for nursing students and to examine its effects, focusing on the accuracy of their perf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 23 publications
(25 reference statements)
1
6
0
Order By: Relevance
“…Our findings that NFF is not inferior to FF education for CPR knowledge and skills is consistent with those of previous studies [ 9 , 10 , 20 , 21 ]. The successful outcome on post-training assessment for both groups might reflect the fact that all students in the study sample had at least one BLS training experience, as they were third-year medical students.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Our findings that NFF is not inferior to FF education for CPR knowledge and skills is consistent with those of previous studies [ 9 , 10 , 20 , 21 ]. The successful outcome on post-training assessment for both groups might reflect the fact that all students in the study sample had at least one BLS training experience, as they were third-year medical students.…”
Section: Discussionsupporting
confidence: 93%
“…With the need for a shift to NFF formats of CPR education, different educational methods have been studied, including the use of video-based and virtual reality training, as well as e-learning modules [ 8 ]. Previous studies have shown that NFF education may not be inferior to FF [ 9 , 10 ] but may be insufficient for skill mastery [ 11 ]. For effective NFF learning, the self-learning ability of students should be evaluated and improved [ 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…The feedback, which these manikins can provide to participants during BLS trainings, has resulted in better compression performance than instructor feedback-based training. 10 , 14 , 15 By using a manikin, which is equipped with a feedback device, it has been shown that self-directed learning is an effective method in gaining the knowledge and skills in trainings with lay adults, as is shown in this study. 10 During the period of contact restrictions, this system was valuable.…”
Section: Discussionmentioning
confidence: 55%
“…The COVID-19 pandemic forced us to shift the methods of CPR education from group-based simulation to self-training with/without virtual-reality or blended learning. [27][28][29] The technological development on CPR education triggered by the COVID-19 pandemic may contribute to improving accessibility and implementation of CPR education.…”
Section: Reinforcing the Survival Environment For Cardiac Arrestmentioning
confidence: 99%